EFFECTIVENESS OF SOURSOP (ANNONA MURICATA) LEAF EXTRACT AS A BOTANICAL PESTICIDE AGAINST ARMYWORM (SPODOPTERA LITURA) ON MUSTARD GREENS (BRASSICA JUNCEA) - Sulaminingsih (PT. Jurnal Center Indonesia Publisher, 2025)
The intensive use of synthetic chemical pesticides in agriculture has led to various negative impacts on the environment and human health, as well as increased pest resistance. As an alternative, plant-based pesticides (botanical insecticides) have shown potential due to their eco-friendly and sustainable nature. This study aims to review the effectiveness of soursop (Annona muricata) leaf extract as a botanical pesticide against the gray caterpillar (Spodoptera litura) on mustard plants (Brassica juncea), using a literature review method. Data were collected through a systematic search of accredited national and international scientific journals, then analyzed descriptively and comparatively. The findings indicate that soursop leaves contain bioactive compounds such as acetogenins, flavonoids, and saponins, which act as stomach poisons, antifeedants, and repellents to S. litura. Several studies reported that extracts from Annona spp. leaves and seeds effectively inhibit larval growth, reduce feeding activity, damage digestive tissues, and lead to larval death. This effectiveness highlights the potential of soursop leaves as a safe and efficient candidate for botanical pesticide development. The study also identifies a research gap regarding field-scale testing on mustard plants, suggesting the need for further agronomic validation.